2010
DOI: 10.1111/j.1471-1842.2010.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information on adverse effects: a systematic review

Abstract: Background: Systematic reviews can provide accurate and timely information on adverse effects. An essential part of the systematic review process is a thorough search of the literature. This often requires searching many different sources. However, it is unclear which sources are most effective at providing information on adverse effects. Objective: To identify and summarise studies that have evaluated sources of information on adverse effects. Methods: Studies were located by searching in 10 databases as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 44 publications
(148 reference statements)
0
27
1
Order By: Relevance
“…There are numerous specialist databases for drug information and adverse effects data that are rarely searched in the 849 systematic reviews. In addition, 20% of reviews only search MEDLINE, yet research has indicated that MEDLINE is not the most fruitful source of adverse effects data and that searching a range of sources is necessary . In one case study, Science Citation Index (SCI) was identified as the most useful database for a drug related adverse effects review, followed by BIOSIS previews and EMBASE, yet these databases are included in 5%, 8% and 54% of the reviews here, respectively …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous specialist databases for drug information and adverse effects data that are rarely searched in the 849 systematic reviews. In addition, 20% of reviews only search MEDLINE, yet research has indicated that MEDLINE is not the most fruitful source of adverse effects data and that searching a range of sources is necessary . In one case study, Science Citation Index (SCI) was identified as the most useful database for a drug related adverse effects review, followed by BIOSIS previews and EMBASE, yet these databases are included in 5%, 8% and 54% of the reviews here, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Guidance indicates that different resources may need to be accessed for systematic reviews of adverse effects compared with systematic reviews of effectiveness . For instance, specific adverse effects databases, such as TOXLINE, or drug databases, such as Derwent Drug File, may be appropriate, and MEDLINE may not be the most relevant source for adverse effects . Other sources of information may also be particularly useful in identifying adverse effects data, such as the Food and Drug Administration (FDA) website, textbooks (such as Meyler's Side Effects of Drugs), bulletins (such as Medicines Safety Update) and industry data …”
Section: Introductionmentioning
confidence: 99%
“…Previous comparative evaluations on safety data sources have focused on the adverse effects of drug interventions (9). Although this is, to our knowledge, the only evaluation of safety data sources for a medical device, this evaluation can be compared with other studies of search strategies for retrieving adverse effects data (8;9).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of comparative evaluations of data sources for adverse effects identified nineteen studies, the majority of which were concerned with adverse drug reactions, with none evaluating sources for safety data on medical devices (9). A systematic review of comparative evaluations of data sources for adverse effects identified nineteen studies, the majority of which were concerned with adverse drug reactions, with none evaluating sources for safety data on medical devices (9).…”
mentioning
confidence: 99%
“…Whilst early research suggests that the Derwent Drug File may have some value [27] more recent research suggests that generic bibliographic databases as described above may provide the highest yield [20].…”
Section: (For Example 'Nausea and Vomiting' 'Gastrointestinal Bleedimentioning
confidence: 99%